A cobalt-substituted Keggin-type polyoxometalate for catalysis of oxidative aromatic cracking reactions in water. Issue 23 (19th October 2020) - Shimoyama, Yoshihiro; Tamura, Satoru; Kitagawa, Yasutaka; Hong, Dachao; Kon, Yoshihiro
Abstract : Oxidative aromatic cracking reactions in water were achieved using a catalytic system with a cobalt-substituted Keggin-type polyoxometalate as a catalyst, an Oxone® as a sacrificial oxidant and sodium bicarbonate as an additive under mild conditions. Abstract : Efficient detoxification of harmful benzene rings into useful carboxylic acids in water is indispensable for achieving a clean water environment. We report herein that oxidative aromatic cracking (OAC) reactions in water were achieved using a catalytic system with a cobalt-substituted Keggin-type polyoxometalate (Co-POM ) as a catalyst, an Oxone® monopersulfate compound as a sacrificial oxidant and sodium bicarbonate as an additive under mild conditions. Sodium bicarbonate plays a crucial role in the selective OAC reactions by Co-POM using ethylbenzenesulfonate as a model substrate. The reactive species was characterized to be a cobalt(iii )-oxyl species based on 31 P NMR, UV-vis spectroscopic, kinetic, and theoretical analyses. The electrophilicity of the cobalt(iii )-oxyl species was demonstrated by a linear relationship with a negative slope in the Hammett plots of initial rates obtained from the OAC reactions of m -xylenesulfonate derivatives. Besides, we have verified the degradation pathway of the OAC reactions using benzene as a model substrate in the catalytic system. The degradation was initiated by an electrophilic attack of the cobalt(iii )-oxyl species on benzene to yield phenol followed by producing catechol, muconic acid, maleic/fumaric acid, tartaric acid derivatives and formic acid on the basis of 1 H NMR spectroscopic analysis.